Defatted Biomass of the Microalga, Desmodesmus sp., Can Replace Fishmeal in the Feeds for Atlantic salmon - Kiron, Viswanath; Sørensen, Mette; Huntley, Mark; Vasanth, Ghana K.; Gong, Yangyang; Dahle, Dalia; Palihawadana, Anjana M. (Frontiers in Marine Science, 2016)
Microalgal biomass is a potential feed ingredient that can replace fishmeal and ensure sustainability standards in aquaculture. To understand the efficacy of the defatted biomass from the marine microalga, Desmodesmus sp. a 70-day feeding study was performed with Atlantic salmon (Salmo salar) smolts. Three groups of fish (av. wt. 167 g) were offered either a control feed (without the microalga) or the microalga-containing (10/20%) feeds. At the end of the feeding period, the growth indices (condition factor, specific growth rate) and survival of the microalga-fed fish were not significantly different from the respective values of the control fish, but the feed conversion ratios were inferior. The proximate composition of the whole body of salmon from the three groups did not vary significantly. Compared to the control fish, the alga-fed fish had lower lipid content (10% alga-fed fish) in their fillet. The protein and lipid digestibility in the three feeds did not differ significantly, but the digestibility of energy in the 10% alga-feed was significantly lower than that of the control feed. Furthermore, comparison of the distal intestinal proteome of Atlantic salmon revealed that the expressions of Alpha-2-HS-glycoprotein-like (Ahsg), Myosin-11 isoform X1 (My11) and Dihydrolipoyl dehydrogenase, mitochondrial-like (Dld) were altered by the microalgal feeding. Examination of the physiological status of the fish based on the serum antioxidant capacities did not reveal any alga-feed-related differences. Moreover, the expression of the selected immune and inflammatory marker genes and the micromorphological observations did not indicate any aberration in the intestinal health of the microalga-fed fish. It is possible to include 20% of defatted Desmodesmus sp. in the feeds of Atlantic salmon.